2020
DOI: 10.1021/acsomega.0c03271
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric Analysis–Fourier Transform Infrared Spectroscopy Study on the Effect of Extraction Pretreatment on the Pyrolysis Properties of Eucalyptus Wood Waste

Abstract: Eucalyptus wood is one of the important hardwood resources with attractive properties of rapid growth and good quality, which are widely used for the manufacture of wood-based boards, furniture, pulp and paper, and so on. In order to explore the potential of sawdust waste from the eucalyptus wood furniture factory as a bioenergy feedstock, its pyrolysis properties after different solvent extractions were examined using thermogravimetric analysis coupled with Fourier transform infrared spectrometry. The mass ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Pyrolysis Real-time monitoring of evolved volatiles from the pyrolysis of flax straw biomass was conducted using FTIR at a heating rate of 20 • C min −1 , as shown in Figure 8a,b, displaying diverse peaks within the range of wavenumbers from 650 to 4000 cm −1 . Different decomposition reactions occur during the biomass pyrolysis process, including decarboxylation, decarbonylation, demethylation, demethoxylation, and dehydration in the pyrolysis stage [69]. The primary pyrolysis products identified from flax straw were carboxylic acids, aldehydes, methane, carbon mono and dioxide, alcohols, aromatics, and ethers [70].…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…Pyrolysis Real-time monitoring of evolved volatiles from the pyrolysis of flax straw biomass was conducted using FTIR at a heating rate of 20 • C min −1 , as shown in Figure 8a,b, displaying diverse peaks within the range of wavenumbers from 650 to 4000 cm −1 . Different decomposition reactions occur during the biomass pyrolysis process, including decarboxylation, decarbonylation, demethylation, demethoxylation, and dehydration in the pyrolysis stage [69]. The primary pyrolysis products identified from flax straw were carboxylic acids, aldehydes, methane, carbon mono and dioxide, alcohols, aromatics, and ethers [70].…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…Through retrieval, it is found that the application of thermogravimetric analysis (Bajaj et al, 2020;Chen et al, 2020b;Gong et al, 2021;Ingale et al, 2020;Moseson et al, 2020;Olopade et al, 2020;Porshnov et al, 2020;Pyra et al, 2020;Ren et al, 2020;Wu et al, 2020) technology in the evaluation of condiment combustion stability has not been reported. Therefore, the research on the combustion heat and thermogravimetric analysis of condiments has important theoretical and practical significance,which can make up for the gaps in this area and provide scientific basis and research significance for the study of condiment quality.…”
Section: Entropy Analysis and Grey Correlation Coefficient Cluster An...mentioning
confidence: 99%
“…2 The liquid product can be further generated into biofuel or used to manufacture highvalue chemicals, and gases can be burned directly to provide a heat source or used to produce syngas. 13 The pyrolysis of biomass material like waste wood can reduce CO 2 emissions 14−16 through the beneficial utilization of its products. However, the technology may also have negative impacts on the environment, 17 such as producing nitrogen oxides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Char can be utilized to produce activated carbon, , soil amendment, electrode material, and graphene production . The liquid product can be further generated into biofuel or used to manufacture high-value chemicals, and gases can be burned directly to provide a heat source or used to produce syngas …”
Section: Introductionmentioning
confidence: 99%